Aquimarina amphilecti sp. nov., isolated from the sponge Amphilectus fucorum - Kennedy, J.; Margassery, L.; O'Leary, N.; O'Gara, Fergal; Morrissey, J.; Dobson, A. (Society for General Microbiology, 2014)
A Gram staining negative, rod-shaped orange-coloured, catalase and oxidase positive, non-motile bacterium designated as 92VT was isolated from the marine sponge, Amphilectus fucorum, collected from Lough Hyne, Co. Cork, Ireland. 16S rRNA gene sequence analysis revealed that strain 92VT clustered with members of the family Flavobacteriaceae, the closest member being Aquimarina latercula NCIMB 1399T, with a gene sequence similarity of 97.5%. Strain 92VT requires seawater for growth with optimal growth occurring at 25°C, pH 6-7 and 3 % (w/v) NaCl. MK-6 is the sole respiratory quinone present and the major fatty acids are iso-C17:0 3-OH, iso-C15:0, iso-C17:1 ?9c and iso-C15:0 3-OH. The DNA G+C content is 36.1 Mol%. Combined phenotypic differences and phylogenetic analysis indicate that strain 92VT represents a novel species of the genus Aquimarina, for which the name Aquimarina amphilecti sp. nov is proposed with strain 92VT as the type strain (=NCIMB 14723T = DSM 25232 T).